2018
DOI: 10.1523/jneurosci.0953-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Form of LOTUS inhibits Nogo Receptor-Mediated Signaling by Interfering with the Interaction Between Nogo Receptor Type 1 and p75 Neurotrophin Receptor

Abstract: Nogo receptor type 1 (NgR1) is known to inhibit neuronal regeneration in the CNS. We have previously identified lateral olfactory tract usher substance (LOTUS) interacts with NgR1 and inhibits its function by blocking its ligand binding. Therefore, LOTUS is expected to have therapeutic potential for the promotion of neuronal regeneration. However, it remains unknown whether the soluble form of LOTUS (s-LOTUS) also has an inhibitory action on NgR1 function as a candidate for therapeutic agents. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…; Kawakami et al . ,b). This converts an inhibitory environment to an attractive environment for neural growth favoring axonal elongation (Kurihara et al .…”
Section: Directional Cues Provided By Agismentioning
confidence: 99%
“…; Kawakami et al . ,b). This converts an inhibitory environment to an attractive environment for neural growth favoring axonal elongation (Kurihara et al .…”
Section: Directional Cues Provided By Agismentioning
confidence: 99%
“…Glycosaminoglycans (GAGs) are linear polysaccharides consisting of repeating disaccharide units and modified with sulfate groups at various positions on the sugar residues. The GAG chains retain negatively charged domains due to characteristics of the sulfate groups, allowing for the absorption of water and other positively charged soluble ligands, such as chemokines (1,2), cytokines (3), growth factors (4,5), and cell surface receptors (6,7). They are classified into chondroitin sulfate/dermatan sulfate (CS/DS), heparin/heparan sulfate (HP/HS), hyaluronan (HA), and keratan sulfate (KS).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the soluble form of LOTUS (s‐LOTUS) is secreted from the membrane‐bound form of LOTUS by cutting of the C‐terminal edge of LOTUS with protease. s‐LOTUS also shows the same potent antagonism for NgR1 function induced by all five of its ligands . These findings indicate that LOTUS is an endogenous potent NgR1 antagonist.…”
Section: Discovery Of a Natural Agent Overcoming Agi: Lotusmentioning
confidence: 62%
“…A recent study of LOTUS‐TG rats also showed the promotion of anatomical and physiological neuronal regeneration and functional recovery after unilateral pyramidotomy . As mentioned before, s‐LOTUS shows the same antagonistic activity against NgR1 as the membrane‐bound form of LOTUS, as well as intravitreal injection of s‐LOTUS, which can be detected in the optic nerve around the injury site, promotes axonal regeneration after optic nerve crush injury in mice . In addition to purified protein administration, LOTUS overexpression due to intravitreal injection of an adeno‐associated virus (AAV) containing LOTUS also promotes axonal regrowth of retinal ganglion cells after optic nerve crush injury .…”
Section: A Novel Strategy Of Neuronal Regeneration Using Physiologicamentioning
confidence: 72%